Phylogenetic Analysis of Rasbora spp. Based on the Mitochondrial DNA COI gene in Harapan Forest - Ahmad Subari; Abdul Razak; Ramadhan Sumarmin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Harapan forest is the remaining lowland tropical forest in Sumatra which represents about 20 percent of the biodiversity on the island of Sumatra. There are several Rasbora species found in the Sungai Kapas Tengah River Refuge in the Harapan Jambi Forest that the relationship is not yet known.This research aims to know kinship and genetic distance several species of Rasbora from Sungai Kapas Tengah, Hutan Harapan Jambi. The method in this research using secondary data from the NCBI website ((National Center for Biotechnology Information). The data taken, namelynucleotide sequence from the Cytochrome Oxidase I (COI) gene in mitochondrial DNA. The Rasbora species analyzed were Rasbora from identification results in the Sungai Kapas Tengah River Refuge, Harapan Jambi Forest, consisting of, Rasbora bankanensis, R. caudimaculata, R. cf. sumatrana, R. dusonensis, R. elegans, R. sumatrana, and R. trilineata. Based on phylogenetic analysis, the location of the branch length in each Rasbora species, the closest kinship is owned byR. sumatrana and R. elegans species. Based on the results of genetic distance analysis, the closest genetic distance was the species R. elegans and R. sumatrana, with a distance value of 0.023 (2.3%). While the farthest genetic distance between R. bankanensis and R. caudimaculata, with a distance value of 0.172 (17.2%).Based on research results It can be concluded that R. bankanensis has a greater kinship and genetic distance value than other Rasbora species, so that this species forms a separate group. Meanwhile, 5 other species have kinship and the value of close genetic distance so that these species are united in the same group. For future researchers, it is hoped that some additional families of fish species will be analyzed for phylogenetic analysis in Sungai Kapas, Hutan Harapan Jambi, so that they can find out the relationship of several other species.